The Capital and the Romantic Sublime: The Case of Thomas De Quincey. Issue 1 (April 2016) - Veliki, Martina Domines
Abstract : This paper aims to explore the idea that the formulation of the modern discipline of economics involved a discourse on the romantic sublime. By using the example of Thomas De Quincey's Confessions of an English Opium-Eater (1821), it will address the issue of money and knowledge as two formative experiences in De Quincey's life. Unlike his literary model, William Wordsworth, who is eager to build up his 'egotistical sublime' (Keats's phrase), De Quincey is intent on registering his traumatic memories and resultant disorders and neuroses. Thus, he builds up a new type of romantic subjectivity where his personal accumulation of debt can be read as an encounter with the sublime, and it runs parallel to Britain's ever-increasing national debt. The sublime in De Quincey's Confessions carries an ideological burden as it affirms the subsistence of a middle-class individual and his right to participate in the discourse of the sublime. However, De Quincey falls from his middle-class position and becomes one of the poor where his access to the sublime experience is utterly denied. De Quincey's London experience is measured against Wordsworth's London experience in The Prelude (1805) and by experiencing the 'negative sublime' (Weiskel), he puts Wordsworthian ethics into practice. Thus, De Quincey's Confessions shows the tensions inherent in the romantic discourse of the sublime in a manner which connects romantic modes of subjectivity to the rising capitalist society.